Filozofia jako terapia w perspektywie biblioterapii - Czernianin, Halina; Czernianin, Wiktor (Publishing House eBooki.com.pl, 2015)
I. Introduction, From advices of autopsychotherapeutical philosophers, through the philosophical psychotherapy, to philosophy as a therapy; I. 1. Stanisław Siek, advices of autopsychotherapeutical philosophers; I. 2. Lech Ostasz, Philosophical Psychotherapy; I. 3. Mateusz Stróżyński, Philosophy as therapy; I. 4. A brief summary; II. Spiritual exercises and therapy; II. 1. The concept of spiritual exercises in the philosophical tradition; II. 2. Summary; III. Phenomenology as a therapy; IV. Summary.
Keywords: bibliotherapy; phenomenology; spiritual exercises; philosophical psychotherapy; philosophy as a therapy